Variation in Rooting Response in Cuttings of Jatropha curcas L. - Ghosh, Lekha; Singh, Lalji; Singh, A.K. (Indian Journal of Agroforestry, 2020)
Clonal propagation is best suited for large scale production of quality planting stock. Studies on rooting of branch cuttings of J. curcas were conducted to evaluate the influence of IBA and different seasons under field conditions. Results revealed that sprouting was maximum (73.30 %) in rainy season and minimum (45.78 %) in winter season. Highest rooting (50.13%) was also found in rainy season followed by those of summer (46.15%) and winter (32.85%) seasons. Number of roots were maximum (3.44) in rainy season and minimum (2.62) in winter season. Again the maximum (7.20 cm) root length was obtained in rainy season and minimum (5.19 cm) in winter season. It was noticed that untreated cuttings performed better than the cuttings treated with 500 mg/l and 1000 mg/l IBA. The findings of the present investigation revealed that among treatments (control, 500 mg/l IBA, 1000 mg/l IBA) tested, untreated (control) cuttings; gave better response; while amongst the three seasons tested, rainy season yielded maximum rooting.